PENGUKURAN EMPLOYEE VOICE - Prihatsanti, Unika; Fajriyanthi, Fajriyanthi; Purwono, Urip (Faculty of Psychology, Diponegoro University, 2019)
Voice as a form of constructive expression in improving organizational functions and effectiveness has received great attention, especially in studies that explain the antecedents and consequences of employees’ voices. However, studies that explain psychometric properties of employee voice measurements are still limited. This article aimed to examine the psychometric properties, particularly construct validity, of employee voice measurement. In Study 1, three employee voice instruments were found through literature review from 23 articles in the last five years (2013-2018) from EBSCOhost and Proquest databases. In Study 2, based on the results of the literature review, the sound psychometric property test was carried out using confirmatory factor analysis. The results of data analysis prove that the Employee Voice scale of Liang, Farh, and Farh (2012) is an appropriate model for measuring employee voices with good validity and reliability.